(untitled) (Scientific Journal of Actuarial Finance and Accounting, 2025)
Green accounting is a new way of including environmental costs in financial decisions, which can greatly help promote sustainable development. This article looks at the significance, challenges, and opportunities of using green accounting in Uzbekistan, a country currently making important changes to its economic and environmental policies. Green accounting is vital for a country's overall growth, especially given the issues of resource depletion and environmental harm. By aligning with global sustainability trends, Uzbekistan can improve its international competitiveness and attract eco-friendly investments. This article contributes to the conversation about sustainable development in Uzbekistan by analyzing how green accounting could transform the country’s economy. Through a thorough review of current literature and practical studies, the article highlights both the theory and practice of implementing green accounting in Uzbekistan. It also offers recommendations for overcoming challenges and maximizing opportunities for sustainable economic growth.